The Relationship between Maternal Knowledge and the Incidence of Temper Tantrums in Toddlers at the Patumbak Health Center in 2024 - Harahap, Nur Afifah; Batubara, Ardiana (Edumaspul: Jurnal Pendidikan, 2025)
Understanding child development is an important aspect that parents must have to optimize child development. Lack of stimulation from parents can cause developmental delays in children. Temper tantrums are unpleasant and disturbing emotional outbursts. The consequences of temper tantrums, for example, a child who vents his frustration by rolling on a hard floor, can cause the child to become injured, venting his anger by hitting his head against the wall, pulling out his hair, and endangering people around him. Temper tantrums can hurt a child’s development, especially if not handled properly. This research aims to determine “The correlation between maternal knowledge and the incidence of temper tantrums in toddlers at the Patumbak Community Health Center in 2024”. This research was quantitative analytical research using cross-sectional analysis. Held from February to March 2024 in the Patumbak Community Health Center working area in 2024. The population was 120 people, and the sample size was 55 using the accidental sampling technique. The research instrument used a questionnaire, and univariate data processing is presented in the form of a frequency distribution table followed by bivariate analysis using SPSS vs 25, then presented descriptively and analytically through statistical tests. The survey results showed that the majority of mothers’ knowledge about temper tantrums in toddler-aged children at the Patumbak Community Health Center was 21 people (38.2%) with poor knowledge, 19 people (34.5%) with sufficient knowledge, and 15 people (27.3%) with good knowledge. From the results of the chi-square test, the value P (0.000) < (0.05) was obtained, which concluded that there was a correlation between maternal knowledge and the incidence of temper tantrums in toddlers at the Patumbak Community Health Center.